একাত্তরের চিঠি - আহমদ, সালাহঊদ্দীন ১৯২৪- (ঢাকা : প্রথমা প্রকাশন, 2009)
Correspondece collection of some martyrs and freedom fighters of the 1971 independence revolution in Bangladesh, written at the time of the revolution.
ARC
Department of Architecture
In Bengali.
Keywords: Revolutionaries -- Bangladesh -- Correspondence; Martyrs -- Bangladesh -- Correspondence; Bangladesh -- History -- Revolution, 1971.